2002
DOI: 10.1109/led.2002.1004233
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of Ru-based alloy gate electrodes for dual metal gate Si-CMOS

Abstract: In this letter, low resistivity Ru and Ru-Ta alloy films, deposited via reactive sputtering, were evaluated as gate electrodes for p-and n-MOSFET devices, respectively. MOSFETs fabricated via a conventional process flow indicated that the work functions of Ru and Ru-Ta alloys were compatible with p-and n-MOSFET devices, respectively. Both of the metal gated devices eliminated gate depletion effects. Good MOSFET characteristics, such as -and mobility, were obtained for both Ru-gated PMOSFETs and Ru-Ta gated NMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…Stacked metal layers used in the gate structure have been investigated. Misra et al [10] reported that a metal gate stack using Ru-Ta alloys could yield a work function compatible with nMOS. Lin et al [11] implanted N into a Mo gate that was suitable for nMOS.…”
Section: Interface Dipole Formation In Mos Stackmentioning
confidence: 99%
“…Stacked metal layers used in the gate structure have been investigated. Misra et al [10] reported that a metal gate stack using Ru-Ta alloys could yield a work function compatible with nMOS. Lin et al [11] implanted N into a Mo gate that was suitable for nMOS.…”
Section: Interface Dipole Formation In Mos Stackmentioning
confidence: 99%
“…However, intrinsic channel DG MOSFETs need to rely solely on gate work function to achieve multiple threshold voltages on a chip due to the absence of body doping, which is an efficient tool to adjust the threshold voltage in DG MOSFETs with doped channels [11,12]. In the past few years, many efforts including implanted metals [13], fully silicided gates [14][15][16], alloy metals [17][18][19], novel high-κ dielectric materials [20] and metal bilayers [21] have been reported, but none has been completely successful in integrating metals with tunable work function in DG MOSFETs due to technological difficulties [22]. Therefore, DG MOSFETs with suitably doped channels seem to be the easiest option from a fabrication point of view, and are seriously being investigated to set appropriate threshold voltages [12,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The three key points for selection of gate electrode materials are work function, thermal stability, and lower resistivity. So far, many types of materials have been investigated to replace poly-silicon, such as pure metals [2][3][4][5][6], binary alloys [7][8][9][10], metal nitrides [11][12][13][14][15], metal carbides [16], and fully silicided Si (FUSI) [17][18][19][20]. Of these, the refractory transition metal nitrides are of interest owing to their good thermal stability, good oxygen diffusion barrier characteristics, and tunable work function.…”
Section: Introductionmentioning
confidence: 99%